Багатотиражні газети 1920–1930‑х рр.: до питання методики історико-джерелознавчого дослідження - Вакульчук, О.; Дубровіна, Л. (Український історичний журнал, 2022)
Мета статті – розкрити специфічні особливості багатотиражних часописів як окремого виду історичних джерел газетного типу, визначити основні методологічні засади та окреслити комплекс емпіричних методик, що дозволяють розкрити джерелознавчий потенціал багатотиражок 1920 – 1930-х рр. Методологія базується на принципах історизму й об’єктивності, системності, використано методи хронологічний, атрибуції, класифікації, систематизації, структурно-функціонального та бібліографознавчого аналізу. Наукова новизна. Уперше розкривається специфіка комплексу багатотиражних газет 1920–1930-х рр. як окремого виду галузевої періодичної преси та об’єкта історичного джерелознавства. Визначено специфічні особливості комплексного дослідження багатотиражок, засобів відображення ними історичної дійсності та можливості вивчення їх інформаційного потенціалу. Висновки. Багатотиражні газети – масові періодичні видання, окремий специфічний вид радянської преси, становлення якого припало на період 1920 – початку 1930-х рр., коли партія й держава розробляли стратегію і тактику реалізації завдань ідеологічного впливу на свідомість «широких мас», організації «соціалістичного будівництва», прискорення економічного розвитку. Величезний пропаґандистський потенціал, закладений у багатотиражних газетах, став полігоном маніпулятивних методів впливу на формування радянської ідеології та посилення контрольної функції партійних органів. Одночасно формувалися нові трудові відносини, ідейний патріотизм працівників, який сприяв згуртованості трудових колективів. Розгалуження структури й розвиток функцій багатотиражних газет, збільшення їх кількості та різновидів відображало цей процес та поступовий рух від відносної самостійності до абсолютної включеності у загал радянської преси. Водночас багатотиражки – це живе джерело місцевого характеру, що може бути розкритим як через використання загальних принципів методології історичної науки, так і з допомогою часткових методик виявлення й атрибуції газет, наукового опису, класифікації та систематизації, інших ознак, що залежали від конкретно-історичних умов, пошуків методів політичного й економічного утвердження радянської влади. The aim of the article is to reveal the specific features of mass-circulation newspapers as a separate type of historical sources of newspaper type, to determine the basic methodological principles and to outline a set of empirical methods to reveal the source potential of masscirculation newspapers of the 1920s – 1930s. The methodology is based on the principle of historicism and objectivity, systematic approach. The following methods are used: chronological, attribution, classification, systematization, structural-functional and bibliographic analysis. The novelty is to reveal the specifics of the complex of mass-circulation newspapers of the 1920s – 1930s as a separate type of periodical press and an object of historical source studies, which is carried out for the first time. The specific features of the complex research of mass-circulation newspapers, the means of reflecting their historical reality and the possibility of studying their information potential are revealed. Conclusions. Mass-circulation newspapers are mass periodicals, a separate specific type of Soviet press, which dates back to the 1920s – early 1930s, when the Communist Party and the Soviet state developed strategies and tactics for implementing ideological influence on the consciousness of the masses and organizing socialist construction. The enormous propaganda potential of mass-circulation newspapers became a testing ground for manipulative methods of influencing the formation of Soviet ideology and strengthening the control function of party bodies. At the same time, we observe the formation of new labor relations, ideological and local patriotism of employees, which contributes to the cohesion of labor collectives. The branching out of the structure and the development of the functions of mass-circulation newspapers, the increase in their number and variety, reflect this process and the gradual movement from relative independence to absolute integration into the general Soviet press. At the same time, mass-circulation newspapers are a living source of information of local character, regional history, which can be revealed both through the use of general principles of historical science methodology and through partial methods of identifying and attributing newspapers, scientific description, classification and systematization in fuzzy definiteness of the substantive aspect of the information structure of mass-circulation newspapers and other features that depended on the specific historical conditions, the search for methods of political and economic establishment of Soviet power.